Sosialisasi Anti Bullying dan Pentingnya Sikap Tolerance Pada Anak di SDN Mojosarirejo, Mojokerto - Stevanus Wahyudianto Prabowo; Mohamad Sholahuddin; Friska Putri Avianti; Dani Andrian Saputra; Siska Wahyu Anita; Bilqis Adzroo H; Kelvin Mulyana Zulianto; Akhmad Yusuf Ariffudin; Ervina Uswatun K; Retno Eka Sulistin; Shoqibatul Islamia; Siti Hanna Hanifah; Nanda Hari Kusuma; Andy Ramadhan; Devy Purnawanti; Eni Afrianti; Naila Putri Maulana; Dea Intan Putri; Arfawati Ibrahim; Lukmanul Hakim; Christopher Erlangga P; Deni Kurniawan; Zidan Ananda Rio V; Satria Heriswana Y; Adella Giovana (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Community Service through real work lectures is an activity to solve a problem that exists in the village. This study aims to provide education to students at school, one of which is about bullying and the impact of bullying in the school environment. This KKN activity was carried out in Mojosarirejo Village, Kemlagi District, Mojokerto Regency. Through KKN, students can apply the knowledge and skills they have acquired in college into real practice, thereby improving their abilities and experience. The methods used in this study use observation and interview methods. The results of this study show that children at elementary school level (SD) understand the impact of bullying which can affect the child’s psychological condition as well as their physical condition. And they do not repeat things related to bullying that can harm themselves and others.